Perubahan Perilaku Siswa Sekolah Dasar di Kota Tidore Kepulauan yang Mengalami Kecanduan Game Online serta Dampaknya Terhadap Prestasi Belajar - Dana Arif Lukmana; Mawardi Djamaluddin (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2023)
The development of science and technology has an effect on behavior change in each student. One of them is that the freedom to access online games has a significant impact on children. The increasing number of cases of online game addiction in children is one of the problems that must be solved by many parties. This problem is part of the moral responsibility of the government, education stakeholders, and parents. This study aims to identify forms of behavioral change in elementary school students who are addicted to online games and their impact on learning outcomes. This research is a descriptive qualitative research with a case study approach which the data collection process is through in-depth interviews and documentation. The subjects of this research are two students, one counselor, and parents. The research data collection instrument used interview guidelines. Then, the research data were analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion. The results showed that children started playing online games in grade 3 elementary school by showing a form of behavior change, often playing online games when they came home from school, playing at school without being caught by the teacher, and playing online games and not interacting with their peers because they prefer to play games. on line. Forms of handling classroom teachers include providing socialization about the negative impact of playing online games, providing motivations for students in particular (students who are addicted to online games), and involving parents to deal with students who are addicted to online games. The forms of parental handling include providing positive activities, limiting the use of cellphones, establishing two-way communication between parents and children, and collaboration with homeroom teachers. Online games have an effect on learning focus but do not show a significant effect on learning outcomes.